Evaluation of indication and feto-maternal outcome of caesarean section among the preterm pregnant patients in a tertiary care hospital - Meherunnesa, Syeda; Akter, Tahmina; Nazim, Roksana; Mafruha Begum, Umme Aoufa; Begum, Morsheda; Showkat Imran, Mostofa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Caesarean sections performed appropriately and following appropriate medical indications are potentially life-saving procedures. At the same time, in many settings, women are increasingly subjected to caesarean sections without any appropriate indication which may contribute to the worldwide secular trend towards higher rates of caesarean sections. The objective of this study was to find out the indications and outcome of caesarean section in preterm pregnant patient. Methods: It was a prospective cross sectional observational study carried out department of obstetrics and gynecology, Dhaka Medical College and Shaheed Suhrawardy Medical College Hospital, Dhaka, during the period of July 2013 to December 2013. Results: Maximum (38%) of patients were between the age group 15-20 years. Of the 100 patients, eclampsia was highest (22%) among the list. Other common indications were APH 8%, PROM 20%, fetal distress 14%, malpresentation with cord prolapse 1%. Emergency operations were performed in majority (95%) of the mothers and elective operations in rest (5%) of the mothers. It was observed that pulmonary oedema 6%, post-partum hemorrhage 8%, wound infection 12% and urinary tract infection was present in 5% cases. Of the 92% had live birth, 8% had still birth and 18% died in the early neonatal period. LBW were 89% and 18% had birth asphyxia. Conclusions: This study showed most common indications were eclampsia, pre-eclampsia. Other common indications were APH, PROM, fetal distress, malpresentation with cord prolapse etc. Electronic foetal monitoring and biochemical testing have improved the foetal assessment to a great extent.